Nontarget Catches of Green and Brown Lacewings (Insecta: Neuroptera: Chrysopidae, Hemerobiidae) Collected by Light- and Volatile-Baited Traps in the Transcarpathian Lowland (W Ukraine) - Kálmán Szanyi; Antal Nagy; Aletta Ősz; Levente Ábrahám; Attila Molnár; Miklós Tóth; Szabolcs Szanyi (Insects)
Distribution data on the lacewing fauna of the data-deficient Transcarpathian Lowland (West Ukraine) were provided. The attractivity of phenylacetaldehyde-(FLO) and isoamyl alcohol-based (SBL) lures designed for trapping lepidopteran pests to lacewings was also studied and compared to the efficiency of light traps traditionally used in studies on neuropterans. In the three-year study, 374 individuals of 10 species were caught. Although the light trap was the most efficient method, the efficiency of the tested lures could also be proved. Regarding abundances, FLO was significantly more efficient than the SBL lure. The lures could supplement the checklist of the fauna with two species and attracted an especially high number of Chrysoperla species. In the case of parallel use with light traps, they serve as an efficient standardised combined method for trapping lacewings, both in faunistic studies and plant protection applications.